Improving propagation of Echinacea purpurea and its content of some active compounds by using Tyrosine and Salicylic acid in vitro (Baghdad Science Journal, 2023)
The seed propagation is the predominant method of Echinacea propagation, which has been criticized for its time-consuming control over the separation factor and the uncertainty of pathogen-free plants produced by this method. The technology of tissue culture has provided multiple opportunities for the production of secondary metabolites continuously without being restricted to a specific season, due to the possibility of controlling the environmental conditions and the components of the nutrient medium needed by the plant. This study was conducted to investigate the effects of salicylic acid as elicitor and tyrosine as precursor on propagation and some secondary compounds production in coneflower in vitro. The result showed the superiority of 2 mg / liter SA over the other treatments, which gave the highest average number of branches formed reaching 33.6 branches / plant part, number of leaves 33.6 leaves/vegetable part, fresh 1.067g and dry 0.058g weights as well as echinacoside concentration  of 291.3427 μg / g DW. However, the treatment 100 mg/l tyrosine gave a maximum of average number of branches 11.80 branches / plant part, number of leaves 11.80 leaves/vegetable part, fresh and dry weight 0.152 and 0.023 g respectively. Concerning echinacoside value, its maximum 318.5203 μg / g DW was recorded with 150 mg/l tyrosine. From this study, we concluded that caffeic acid derivatives such as echinacosides are one of the main phytochemical components of Echinacea extracts. The system of cell culture is a tool for the large-scale, year-round culture of plant cells, so it is a continuous source for the production of active compounds